The technology of Copper Age funerary pottery from Central Italy: An integrated study of compositional analyses and manufacturing traces. (1st April 2020) - Forte, V.; Tarquini, O.; Botticelli, M.; Medeghini, L.
Abstract : The paper focuses on ceramic vessels unearthed from Copper Age necropolises located in the area of the modern city of Rome and commonly attributed to the Rinaldone culture . The peculiar vessels' shapes, mainly associated with the consumption of beverages, their accuracy of manufacture and the very low impact of these ceramic morphologies in the coeval household assemblages lead to the study of such an apparently selected production through a multidisciplinary research. Petrographic analysis, X‐ray fluorescence (XRF) and X‐ray diffraction (XRD) integrated with the analysis of manufacturing traces and X‐ray investigation suggest the transmission of technological choices, which remained unchanged over almost two millennia.